Understanding the barriers and facilitators to implementing and sustaining Mobile Overdose Response Services from the perspective of Canadian key interest groups: a qualitative study - Boogyung Seo; Nathan Rider; William Rioux; Adrian Teare; Stephanie Jones; Pamela Taplay; S. Monty Ghosh (BMC, 2024)
Abstract Introduction Unregulated supply of fentanyl and adulterants continues to drive the overdose crisis. Mobile Overdose Response Services (MORS) are novel technologies that offer virtual supervised consumption to minimize the risk of fatal overdose for those who are unable to access other forms of harm reduction. However, as newly implemented services, they are also faced with numerous limitations. The aim of this study was to examine the facilitators and barriers to the adoption of MORS in Canada. Methods A total of 64 semi-structured interviews were conducted between November 2021 and April 2022. Participants consisted of people who use substances (PWUS), family members of PWUS, health care professionals, harm reduction workers, MORS operators, and members of the general public. Inductive thematic analysis was used to identify the major themes and subthemes. Results Respondents revealed that MORS facilitated a safe, anonymous, and nonjudgmental environment for PWUS to seek harm reduction and other necessary support. It also created a new sense of purpose for operators to positively contribute to the community. Further advertising and promotional efforts were deemed important to increase its awareness. However, barriers to MORS implementation included concerns regarding privacy/confidentiality, uncertainty of funding, and compassion fatigue among the operators. Conclusion Although MORS were generally viewed as a useful addition to the currently existing harm reduction services, it's important to monitor and tackle these barriers by engaging the perspectives of key interest groups.